High-flux power battery positive electrode material and preparation method thereof
By forming high-nickel phases and low-nickel phases in the positive electrode material of lithium-ion battery, and using catechol coating and zirconium dioxide modification technology, the lithium-nickel mixed discharge problem is solved, and the cycle life and fast charging performance of the battery are improved.
Patent Information
- Application Number
- CN202411689250.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-11-25
AI Technical Summary
In lithium-ion batteries, the increase in nickel content leads to an intensification of lithium-nickel mixed discharge phenomenon, affecting the charging and discharging performance and cycle life of the battery, and is particularly prominent in fast-charging battery applications.
By dividing the nickel source into two parts of varying sizes and different treatments, the high-nickel phase and low-nickel phase are formed. The distribution of nickel elements in the crystal is changed and the nickel ions are guided to Internal reequilibrium migration is performed between the high-nickel phase and the low-nickel phase to reduce the migration of nickel ions to the lithium layer.
It effectively suppresses the phenomenon of mixed discharge of nickel and lithium, improves the long-term circulation and fast charging performance of the battery, and extends the service life of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy battery electrode materials technology, and in particular to a high-throughput power battery cathode material and its preparation method. Background Art
[0002] Traditional gasoline-powered vehicles are highly dependent on fossil fuels such as oil. With increasing global energy consumption and dwindling fossil fuel reserves, the energy crisis is becoming increasingly prominent. Finding alternative clean energy sources has become a crucial direction for global energy development. Electric vehicles, as a mode of transportation powered by electricity, have enormous potential in reducing dependence on fossil fuels. The driving range of electric vehicles is a key concern for consumers, and improving the energy density of power batteries is crucial for increasing driving range. The performance of cathode materials directly determines the energy density of power batteries; therefore, developing cathode materials with high specific capacity and high voltage is an important way to improve the energy density of power batteries.
[0003] Currently, the most widely used commercially available cathode materials for lithium-ion batteries include lithium cobalt oxide, lithium iron phosphate, and ternary materials. Among them, lithium cobalt oxide has a higher cost; lithium iron phosphate has a lower specific capacity; and ternary materials (Li(NiCoMn)O2 or Li(NiCoAl)O2) are widely used in power lithium batteries due to their advantages such as controllable cost, high energy density, good cycle performance, and long cycle life.
[0004] In NCM ternary materials, nickel plays a crucial role in increasing the material's volumetric energy density. As the nickel content increases, the specific capacity of the ternary material also improves. For example, upgrading from the common NCM523 (nickel-cobalt-manganese ratio of 5:2:3) to NCM811 (nickel-cobalt-manganese ratio of 8:1:1) significantly enhances the specific capacity. However, increasing the nickel content can lead to lithium-nickel mixing. During charging and discharging, some nickel ions occupy lithium ion positions, hindering normal lithium ion transport. This not only affects the battery's charge and discharge performance but also accelerates capacity decay and reduces cycle life.
[0005] Especially with the increasing consumer demand for fast-charging batteries, one of the most pressing technical challenges manufacturers face in developing fast-charging batteries is that continuous rapid charging exacerbates lithium-nickel mixing. To ensure the performance of fast-charging batteries, it is necessary to reduce the occurrence of lithium-nickel mixing. Summary of the Invention
[0006] To address the problems mentioned in the background art, the high-throughput power battery cathode material provided by this invention uses a special process to separate the internal crystal structure of the cathode material into a high-nickel phase and a low-nickel phase. Nickel ions tend to be transported in different nickel phases, avoiding nickel ions from occupying the positions of lithium ions and effectively reducing the occurrence of lithium-nickel mixing. This cathode material can be widely used in fast-charging batteries.
[0007] Specifically: A method for preparing a high-throughput power battery cathode material, comprising the following steps: Step 1: Weigh the nickel source, cobalt source, manganese source, and lithium source. Divide the nickel source into two portions of unequal weight for later use. Step 2: Prepare solutions of nickel, cobalt, and manganese sources in large quantities, and mix the solutions to form a mixed salt solution. Add the reaction base liquid to the reactor. Under stirring, simultaneously add the mixed salt solution, precipitant solution, and complexing agent solution to the reactor for reaction. Control the pH value of the reaction at 10-12. After the reaction is completed, filter to separate the precursor, wash and dry it for later use. Step 3: Mix the precursor and lithium source evenly and perform the first sintering to obtain the first sintered product; Step 4: Prepare a nickel salt solution from a small amount of nickel source; add the reaction base liquid to the reactor, and under stirring conditions, simultaneously add the nickel salt solution, precipitant solution, and complexing agent solution to the reactor for reaction. Control the pH value of the reaction at 10-12. After the reaction is completed, filter to separate the nickel precipitate, wash and dry it for later use. Step 5: Add nickel precipitate to catechol solution, adjust solution to alkaline, and react under stirring. After coating is complete, slowly add zirconium dioxide suspension under stirring to continue reaction. After reaction is complete, filter to separate solid, wash and dry for later use. Step 6: Mix the solid product obtained in Step 5 with the first sintering product obtained in Step 3 and sinter them evenly to obtain a high-throughput power battery cathode material.
[0008] In step one, nickel, cobalt, and manganese sources are weighed according to a nickel-cobalt-manganese molar ratio of 5-8:1-2:1-3; lithium sources are weighed according to a lithium molar to nickel-cobalt-manganese total molar ratio of 1-1.1:1; the nickel source is divided into two parts of unequal weight, with the larger part to the smaller part having a weight ratio of 7-9:1; nickel sulfate or nickel nitrate is selected as the nickel source, cobalt sulfate or cobalt nitrate is selected as the cobalt source, manganese sulfate or manganese nitrate is selected as the manganese source, and lithium carbonate is selected as the lithium source. In step two, the concentration of the nickel source solution is 1–1.5 mol / L; the concentration of the cobalt source solution is 0.8–1 mol / L; and the concentration of the manganese source solution is 1–1.2 mol / L.
[0009] Furthermore, in steps two and four, Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 1% to 3% and a mass concentration of 25% to 28% for the ammonia water. Preparation of precipitant solution: Sodium hydroxide aqueous solution with a mass concentration of 25%–30%; Preparation of complexing agent solution: ammonia water with a mass concentration of 15% to 25%.
[0010] Furthermore, in step two, the dropping rate of the mixed salt solution is 5–10 L / min, the dropping rate of the precipitant solution is 10–20 L / min, and the dropping rate of the complexing agent solution is 5–20 L / min, until the mixed salt solution is completely added.
[0011] Furthermore, in step three, the first sintering temperature is 500-550℃. The furnace temperature is first raised to the set temperature at a heating rate of 2-4℃ / min, and then the sintering time is maintained at the set temperature for 10-12 hours. In step six, the second sintering temperature is 600-700℃. The furnace temperature is first raised to the set temperature at a heating rate of 2-4℃ / min, and then the sintering time is maintained at the set temperature for 8-10 hours.
[0012] Furthermore, in step four, the dropping rate of the nickel salt solution is 1–3 L / min, the dropping rate of the precipitant solution is 2–6 L / min, and the dropping rate of the complexing agent solution is 1–6 L / min, until the nickel salt solution is completely added.
[0013] Further, in step five, the catechol solution is prepared as follows: catechol is dissolved in a mixed solution of deionized water and ethanol with a volume ratio of 1 to 2:1, and the concentration of the catechol solution is 1 to 2 g / L; the weight ratio of catechol to nickel precipitate is 0.1 to 0.5:1. Preparation of zirconium dioxide suspension: Nano-sized zirconium dioxide was dispersed in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate was 0.1-0.2:1; the weight ratio of zirconium dioxide to deionized water was 1:40-80.
[0014] Furthermore, in step five, the coating reaction temperature is 30–50°C and the reaction time is 8–12 h; the zirconium dioxide modification reaction temperature is 40–60°C and the reaction time is 4–6 h.
[0015] In addition, the present invention also provides a high-throughput power battery cathode material, which is prepared by the above-described preparation method.
[0016] Compared with the prior art, the beneficial features of the present invention are as follows: 1. The method for preparing high-throughput power battery cathode material provided by this invention involves dividing a nickel source into two portions of unequal size and treating them differently. First, a larger portion of the nickel source is mixed with a cobalt source and a manganese source to prepare a nickel-cobalt-manganese hydroxide precipitate, which is then sintered with lithium carbonate for the first time. Then, a smaller portion of the nickel source is used to prepare a nickel hydroxide precipitate separately, which is subsequently treated with special processes such as catechol coating and zirconium dioxide particle modification before participating in a second sintering. During the second sintering process, the coating layer of the smaller portion of nickel precipitate and the surface-modified zirconium dioxide particles synergistically alter the local reaction environment and element diffusion paths, allowing the smaller portion of nickel to be separated from the larger portion within the crystal. The second sintering product retains its layer. The main crystal structure is a morphological structure, but due to the special treatment of small amounts of nickel precipitation, there are slight adjustments or changes in the structure in local areas. This different treatment method results in differences in the distribution of nickel elements in the two sintering processes, forming high-nickel and low-nickel phases inside the crystal. The reason for nickel-lithium mixing is that the main undesirable migration direction of nickel ions is towards the lithium layer. However, this invention guides nickel ions to migrate more internally between the high-nickel and low-nickel phases by forming high-nickel and low-nickel phases inside the cathode material crystal. This makes the migration trend of nickel ions more inclined from the high-nickel phase to the low-nickel phase rather than towards the lithium layer, effectively reducing the harmful migration of nickel ions to the lithium layer, thereby inhibiting the occurrence of nickel-lithium mixing.
[0017] 2. The method for preparing high-throughput power battery cathode material provided by the present invention has an interfacial energy between the high-nickel phase and the low-nickel phase in the cathode material crystal, which prevents nickel ions from easily migrating. Therefore, even if the battery has been charged and discharged multiple times, the high-nickel phase and the low-nickel phase of the cathode material still exist. The migration trend of nickel ions from the high-nickel phase to the low-nickel phase is higher than the migration trend of nickel ions from the nickel phase to the lithium layer, which ensures the long-term effectiveness of the cathode material in suppressing nickel-lithium mixing.
[0018] 3. The method for preparing high-throughput power battery cathode material provided by this invention involves the following: Catechol readily undergoes oxidative polymerization under alkaline conditions. As the reaction proceeds, the degree of polymerization continuously increases, eventually forming a relatively high molecular weight polymer that is tightly adsorbed onto the surface of the nickel precipitate, thus forming a coating layer. Furthermore, the phenolic hydroxyl groups on the catechol polymer can undergo coordination chemical reactions with metal ions on the surface of zirconium dioxide particles to form coordination bonds, further enhancing the bonding force between the zirconium dioxide particles and the catechol coating layer, making the zirconium dioxide particles more firmly modified on the coating layer. During the sintering process, the catechol polymer coating layer and zirconium dioxide particles hinder the diffusion of nickel from a small amount of nickel precipitate, preventing nickel from being uniformly distributed within the crystal, thus ensuring the formation of both high-nickel and low-nickel phases. DETAILED DESCRIPTION
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] To facilitate implementation of this invention by those skilled in the art, some of the reagents used in the embodiments and comparative examples are now described: Nickel source: Nickel sulfate, Wuhan Jiyesheng Chemical Co., Ltd. Cobalt source: Cobalt sulfate heptahydrate, Wuhan Jiyesheng Chemical Co., Ltd. Manganese source: Manganese sulfate monohydrate, Wuhan Jiyesheng Chemical Co., Ltd. Lithium source: Lithium carbonate, Wuhan Jiyesheng Chemical Co., Ltd. Sodium hydroxide: analytical grade, Langfang Huachen Chemical Co., Ltd. Ammonia solution: 25% ammonia solution, analytical grade, Shandong Shengze Chemical Co., Ltd. Ethanol: Shandong Xinyingshun New Materials; Catechins: Jinan Lanjue Trading Co., Ltd. Zirconium dioxide: Langfang Pengcai Fine Chemical Co., Ltd.
[0021] Example 1
[0022] A method for preparing a high-throughput power battery cathode material, comprising the following steps: S1. Weigh out nickel, cobalt, and manganese sources in a molar ratio of 8:1:1; weigh out lithium sources in a molar ratio of 1.1:1 to the total number of nickel, cobalt, and manganese; divide the nickel sources into two unequal parts, with the larger part being in a weight ratio of 9:1 to the smaller part. S2. Preparation of a large amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L; Preparation of cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L; Preparation of manganese source solution: Dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 3% and a mass concentration of 28% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%; S3. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add the mixed salt solution of nickel-cobalt-manganese source solution, precipitant solution, and complexing agent solution dropwise into the reactor for reaction. The dropwise addition rate of the mixed salt solution is 10L / min, the dropwise addition rate of the precipitant solution is 20L / min, and the dropwise addition rate of the complexing agent solution is 20L / min. The dropwise addition continues until the mixed salt solution is completely added. The pH value of the reaction is controlled at 12, and the reaction is carried out for 20h. After the reaction is completed, filter to separate the precursor, wash and dry it for later use. S4. Mix the precursor and lithium source evenly and perform the first sintering. First, raise the furnace temperature to the sintering temperature of 550℃ at a heating rate of 4℃ / min, and then maintain the sintering time at the set temperature for 12h to obtain the first sintered product. S5. Preparation of a small amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 3% and a mass concentration of 28% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%; S6. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add nickel salt solution, precipitant solution, and complexing agent solution dropwise into the reactor. The dropwise addition rate of nickel salt solution is 3L / min, the dropwise addition rate of precipitant solution is 6L / min, and the dropwise addition rate of complexing agent solution is 6L / min. Continue adding until the nickel salt solution is completely added, and then proceed with the reaction. The pH value of the reaction is controlled at 12, and the reaction is carried out for 20 hours. After the reaction is completed, filter to separate the nickel precipitate, wash and dry it for later use. S7. Preparation of catechin solution: Dissolve catechin in a mixed solution of deionized water and ethanol at a volume ratio of 2:1, so that the concentration of the catechin solution is 2 g / L; the weight ratio of catechin to nickel precipitate is 0.5:1. Preparation of zirconium dioxide suspension: Nano-sized zirconium dioxide was dispersed in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate was 0.2:1; the weight ratio of zirconium dioxide to deionized water was 1:80. S8. Add nickel precipitate to catechol solution, add sodium hydroxide to adjust the pH of the solution to 9, and react under the conditions of stirring at 400 rpm and temperature of 50℃ for 12 hours. After the coating is completed, slowly add zirconium dioxide suspension under the conditions of stirring at 400 rpm and temperature of 60℃ to continue the reaction for 6 hours. After the reaction is completed, filter to separate the solid, wash and dry it for later use. S9. The solid product from S8 and the first sintering product are ball-milled for 4 hours at a speed of 400 rpm. After mixing evenly, the furnace temperature is raised to 700℃ at a heating rate of 4℃ / min. The sintering time is then maintained at the set temperature for 10 hours to obtain high-throughput power battery cathode material.
[0023] Example 2
[0024] A method for preparing a high-throughput power battery cathode material, comprising the following steps: S1. Weigh out nickel, cobalt, and manganese sources according to a nickel-cobalt-manganese molar ratio of 5:2:3; weigh out lithium sources according to a lithium-cobalt-manganese molar ratio of 1:1; divide the nickel sources into two unequal parts, with the larger part being 7:1 in weight to the smaller part. S2. Preparation of a large amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1 mol / L; Preparation of cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 0.8 mol / L; Preparation of manganese source solution: Dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 1% and a mass concentration of 25% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 25%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 15; S3. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add the mixed salt solution of nickel-cobalt-manganese source solution, precipitant solution, and complexing agent solution dropwise into the reactor for reaction. The dropwise addition rate of the mixed salt solution is 5L / min, the dropwise addition rate of the precipitant solution is 10L / min, and the dropwise addition rate of the complexing agent solution is 5L / min. The dropwise addition continues until the mixed salt solution is completely added. The pH value of the reaction is controlled at 10, and the reaction is carried out for 12 hours. After the reaction is completed, filter to separate the precursor, wash and dry it for later use. S4. Mix the precursor and lithium source evenly and perform the first sintering. First, raise the furnace temperature to the sintering temperature of 500℃ at a heating rate of 2℃ / min, and then maintain the sintering time at the set temperature for 10h to obtain the first sintered product. S5. Preparation of small-weight nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 1% and a mass concentration of 25% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 25%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 15%; S6. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 200rpm and temperature of 40℃, simultaneously add nickel salt solution, precipitant solution, and complexing agent solution dropwise into the reactor. The dropwise addition rate of nickel salt solution is 1L / min, the dropwise addition rate of precipitant solution is 2L / min, and the dropwise addition rate of complexing agent solution is 1L / min. Continue adding until the nickel salt solution is completely added, and then proceed with the reaction. The pH value of the reaction is controlled at 10, and the reaction is carried out for 12 hours. After the reaction is completed, filter to separate the nickel precipitate, wash and dry it for later use. S7. Preparation of Catechol Solution: Dissolve catechin in a 1:1 volume ratio of deionized water and ethanol to obtain a catechin solution concentration of 1 g / L; the weight ratio of catechin to nickel precipitate is 0.1:1. Preparation of zirconium dioxide suspension: Nano-sized zirconium dioxide was dispersed in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate was 0.1:1; the weight ratio of zirconium dioxide to deionized water was 1:40. S8. Add nickel precipitate to catechol solution, add sodium hydroxide to adjust the pH of solution to 8, and react under the conditions of stirring at 200 rpm and temperature of 30℃ for 8 hours. After the coating is completed, slowly add zirconium dioxide suspension under the conditions of stirring at 200 rpm and temperature of 40℃ to continue the reaction for 4 hours. After the reaction is completed, filter to separate the solid, wash and dry it for later use. S9. The solid product from S8 and the first sintering product are ball-milled for 2 hours at a speed of 200 rpm. After mixing evenly, the furnace temperature is raised to 600°C at a heating rate of 2°C / min. The sintering time is then maintained at the set temperature for 8 hours to obtain high-throughput power battery cathode material.
[0025] Example 3
[0026] A method for preparing a high-throughput power battery cathode material, comprising the following steps: S1. Weigh out nickel, cobalt, and manganese sources in a molar ratio of 7:1:2; weigh out lithium sources in a molar ratio of 1:1 to the total number of nickel, cobalt, and manganese; divide the nickel sources into two parts of unequal weight, with the ratio of the larger part to the smaller part being 8:1. S2. Preparation of a large amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.3 mol / L; Preparation of cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 0.9 mol / L; Preparation of manganese source solution: Dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.1 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 2% and a mass concentration of 25% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 27%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 20%; S3. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add the mixed salt solution of nickel-cobalt-manganese source solution, precipitant solution, and complexing agent solution dropwise into the reactor for reaction. The dropwise addition rate of the mixed salt solution is 7L / min, the dropwise addition rate of the precipitant solution is 15L / min, and the dropwise addition rate of the complexing agent solution is 10L / min. The dropwise addition continues until the mixed salt solution is completely added. The pH value of the reaction is controlled at 11.2, and the reaction is carried out for 16 hours. After the reaction is completed, filter to separate the precursor, wash and dry it for later use. S4. Mix the precursor and lithium source evenly and perform the first sintering. First, raise the furnace temperature to the sintering temperature of 520℃ at a heating rate of 3℃ / min, and then maintain the sintering time at the set temperature for 11h to obtain the first sintered product. S5. Preparation of a small amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.3 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 2% and a mass concentration of 25% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 27%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 20%; S6. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 300rpm and temperature of 40℃, simultaneously add nickel salt solution, precipitant solution, and complexing agent solution dropwise into the reactor. The dropwise addition rate of nickel salt solution is 2L / min, the dropwise addition rate of precipitant solution is 4L / min, and the dropwise addition rate of complexing agent solution is 4L / min. Continue adding until the nickel salt solution is completely added, and then proceed with the reaction. The reaction pH is controlled at 11, and the reaction is carried out for 15 hours. After the reaction is completed, filter to separate the nickel precipitate, wash and dry it for later use. S7. Preparation of catechin solution: Dissolve catechin in a mixed solution of deionized water and ethanol at a volume ratio of 1.5:1, so that the concentration of the catechin solution is 1.5 g / L; the weight ratio of catechin to nickel precipitate is 0.3:1. Preparation of zirconium dioxide suspension: Nano-sized zirconium dioxide was dispersed in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate was 0.1:1; the weight ratio of zirconium dioxide to deionized water was 1:60. S8. Add nickel precipitate to catechol solution, add sodium hydroxide to adjust the pH of the solution to 8.5, and react under the conditions of stirring at 300 rpm and temperature of 40℃ for 10 hours. After the coating is completed, slowly add zirconium dioxide suspension under the conditions of stirring at 300 rpm and temperature of 50℃ to continue the reaction for 5 hours. After the reaction is completed, filter to separate the solid, wash and dry it for later use. S9. The solid product from S8 and the first sintering product are ball-milled for 3 hours at a speed of 300 rpm. After mixing evenly, the furnace temperature is raised to 650°C at a heating rate of 3°C / min. The sintering time is then maintained at the set temperature for 8 hours to obtain high-throughput power battery cathode material.
[0027] Comparative Example 1 A method for preparing a battery cathode material, comprising the following steps: S1. Weigh out the nickel source, cobalt source, and manganese source according to the molar ratio of nickel, cobalt, and manganese of 8:1:1; weigh out the lithium source according to the molar ratio of lithium to the total number of nickel, cobalt, and manganese moles of 1.1:1. S2. Preparation of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L; Preparation of cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L; Preparation of manganese source solution: Dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 3% and a mass concentration of 28% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%; S3. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add the mixed salt solution of nickel-cobalt-manganese source solution, precipitant solution, and complexing agent solution dropwise into the reactor for reaction. The dropwise addition rate of the mixed salt solution is 10L / min, the dropwise addition rate of the precipitant solution is 20L / min, and the dropwise addition rate of the complexing agent solution is 20L / min. The dropwise addition continues until the mixed salt solution is completely added. The pH value of the reaction is controlled at 12, and the reaction is carried out for 20h. After the reaction is completed, filter to separate the precursor, wash and dry it for later use. S4. Mix the precursor and lithium source evenly and sinter them. First, raise the furnace temperature to 550°C at a heating rate of 4°C / min, and then maintain the sintering time at the set temperature for 12 hours to obtain the cathode material.
[0028] Comparative Example 2 A method for preparing a battery cathode material, comprising the following steps: S1. Weigh out nickel, cobalt, and manganese sources in a molar ratio of 8:1:1; weigh out lithium sources in a molar ratio of 1.1:1 to the total number of nickel, cobalt, and manganese; divide the nickel sources into two unequal parts, with the larger part being in a weight ratio of 9:1 to the smaller part. S2. Preparation of a large amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L; Preparation of cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L; Preparation of manganese source solution: Dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 3% and a mass concentration of 28% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%; S3. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add the mixed salt solution of nickel-cobalt-manganese source solution, precipitant solution, and complexing agent solution dropwise into the reactor for reaction. The dropwise addition rate of the mixed salt solution is 10L / min, the dropwise addition rate of the precipitant solution is 20L / min, and the dropwise addition rate of the complexing agent solution is 20L / min. The dropwise addition continues until the mixed salt solution is completely added. The pH value of the reaction is controlled at 12, and the reaction is carried out for 20h. After the reaction is completed, filter to separate the precursor, wash and dry it for later use. S4. Mix the precursor and lithium source evenly and perform the first sintering. First, raise the furnace temperature to the sintering temperature of 550℃ at a heating rate of 4℃ / min, and then maintain the sintering time at the set temperature for 12h to obtain the first sintered product. S5. Preparation of a small amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 3% and a mass concentration of 28% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%; S6. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add nickel salt solution, precipitant solution, and complexing agent solution dropwise into the reactor. The dropwise addition rate of nickel salt solution is 3L / min, the dropwise addition rate of precipitant solution is 6L / min, and the dropwise addition rate of complexing agent solution is 6L / min. Continue adding until the nickel salt solution is completely added, and then proceed with the reaction. The pH value of the reaction is controlled at 12, and the reaction is carried out for 20 hours. After the reaction is completed, filter to separate the nickel precipitate, wash and dry it for later use. S7. With a zirconium dioxide to nickel precipitate weight ratio of 0.2:1, the nickel precipitate, zirconium dioxide and the first sintering product are ball-milled for 4 hours and the ball milling speed is controlled at 400 rpm. After mixing evenly, the furnace temperature is raised to the sintering temperature of 700℃ at a heating rate of 4℃ / min. Then, the sintering time is maintained at the set temperature for 10 hours to obtain the battery cathode material.
[0029] Comparative Example 3 A method for preparing a battery cathode material, comprising the following steps: S1. Weigh out nickel, cobalt, and manganese sources in a molar ratio of 8:1:1; weigh out lithium sources in a molar ratio of 1.1:1 to the total number of nickel, cobalt, and manganese; divide the nickel sources into two unequal parts, with the larger part being in a weight ratio of 9:1 to the smaller part. S2. Preparation of a large amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L; Preparation of cobalt source solution: Dissolve cobalt sulfate heptahydrate in deionized water to prepare a solution with a concentration of 1 mol / L; Preparation of manganese source solution: Dissolve manganese sulfate monohydrate in deionized water to prepare a solution with a concentration of 1.2 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 3% and a mass concentration of 28% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%; S3. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add the mixed salt solution of nickel-cobalt-manganese source solution, precipitant solution, and complexing agent solution dropwise into the reactor for reaction. The dropwise addition rate of the mixed salt solution is 10L / min, the dropwise addition rate of the precipitant solution is 20L / min, and the dropwise addition rate of the complexing agent solution is 20L / min. The dropwise addition continues until the mixed salt solution is completely added. The pH value of the reaction is controlled at 12, and the reaction is carried out for 20h. After the reaction is completed, filter to separate the precursor, wash and dry it for later use. S4. Mix the precursor and lithium source evenly and perform the first sintering. First, raise the furnace temperature to the sintering temperature of 550℃ at a heating rate of 4℃ / min, and then maintain the sintering time at the set temperature for 12h to obtain the first sintered product. S5. Preparation of a small amount of nickel source solution: Dissolve nickel sulfate in deionized water to prepare a solution with a concentration of 1.5 mol / L; Preparation of the reaction base solution: Mix ammonia water and deionized water at a volume concentration of 3% and a mass concentration of 28% for the ammonia water. Preparation of precipitant solution: Mix sodium hydroxide with deionized water to prepare a sodium hydroxide aqueous solution with a mass concentration of 30%; Preparation of complexing agent solution: Mix ammonia water and deionized water to prepare ammonia water with a mass concentration of 25%; S6. Open the reactor equipped with a three-dimensional paddle stirrer, purge nitrogen into the reactor, and add 50L of reaction base liquid. Under the conditions of stirring at 400rpm and temperature of 40℃, simultaneously add nickel salt solution, precipitant solution, and complexing agent solution dropwise into the reactor. The dropwise addition rate of nickel salt solution is 3L / min, the dropwise addition rate of precipitant solution is 6L / min, and the dropwise addition rate of complexing agent solution is 6L / min. Continue adding until the nickel salt solution is completely added, and then proceed with the reaction. The pH value of the reaction is controlled at 12, and the reaction is carried out for 20 hours. After the reaction is completed, filter to separate the nickel precipitate, wash and dry it for later use. S7. Preparation of catechin solution: Dissolve catechin in a mixed solution of deionized water and ethanol at a volume ratio of 2:1, so that the concentration of the catechin solution is 2 g / L; the weight ratio of catechin to nickel precipitate is 0.5:1. S8. Add nickel precipitate to catechol solution, add sodium hydroxide to adjust the pH of the solution to 9, and react under the conditions of stirring at 400 rpm and temperature of 50℃ for 12 hours. After the coating is completed, filter to separate the solid, wash and dry it for later use. S9. The solid product from S8 and the first sintering product are ball-milled for 4 hours at a speed of 400 rpm. After mixing evenly, the furnace temperature is raised to 700℃ at a heating rate of 4℃ / min. The sintering time is then maintained at the set temperature for 10 hours to obtain the battery cathode material.
[0030] To verify the beneficial effects of the present invention, the cathode materials obtained in the above embodiments and comparative examples need to be tested.
[0031] Test items: Test the original nickel-lithium mixing rate of the cathode material, that is, the nickel-lithium mixing rate before assembly; then use the cathode material to assemble a battery, perform fast charging cycles on the battery, and then disassemble and test the nickel-lithium mixing rate of the cathode material after fast charging cycles.
[0032] Battery Assembly: The positive electrode material, conductive agent SuperP, and binder PVDF were dissolved in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to form a slurry. This slurry was then coated onto aluminum foil using an automated coating machine. After vacuum drying for 12 hours, the slurry was cut into positive electrode sheets. These sheets were then assembled into coin cells using standard process conditions. The coin cell specification was CR2023, the negative electrode was a lithium sheet, the separator was a polypropylene membrane, the electrolyte solvent was a 1:1 volume ratio EC / DEC mixed solvent, the conductive salt was 1M lithium hexafluorophosphate, the coin cell encapsulation pressure was 800 Pa, and the encapsulation time was 5 seconds.
[0033] Test batteries were assembled using the cathode materials of Examples 1-3 and Comparative Examples 1-3 according to the battery assembly method described above. Three test batteries were fabricated for each set of examples or comparative examples.
[0034] Each group has three test batteries: one battery completes 50 constant current charge-discharge cycles, one completes 100 constant current charge-discharge cycles, and one completes 200 constant current charge-discharge cycles. Test conditions are 40°C, 4.6–3.0V voltage range, 3C charging / 0.3C discharging. Capacity retention and nickel-lithium mixing ratio are measured during the test cycles.
[0035] Nickel-lithium mixed-electrode detection: X-ray diffraction (XRD) is used for detection; pre-assembly detection directly tests the positive electrode material; post-assembly detection requires disassembling the battery to separate the positive electrode material, grinding the positive electrode material and drying it at 70°C for 10 hours before preparing a sample for detection.
[0036] The test results above show that the nickel ion mixing rate of Examples 1-3 after fast charging test is significantly lower than that of Comparative Examples 1-3. Therefore, the technical solution of the present invention can effectively reduce the occurrence of nickel ion mixing.
[0037] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-throughput power battery positive electrode material, characterized in that: The steps include: Step 1, weigh the nickel source, cobalt source, manganese source and lithium source, and divide the nickel source into two parts of unequal weight for later use; Step 2: Prepare solutions of nickel source, cobalt source and manganese source in large weight portions respectively, and mix the solutions of the three to form a mixed salt solution; add the reaction base liquid to the reactor, and under stirring, dropwise add the mixed salt solution, precipitant solution and complexing agent solution into the reactor at the same time to react, and control the reaction pH value to be 10-12. After the reaction is completed, filter to separate the precursor, wash and dry it for later use; Step 3, mixing the precursor and the lithium source uniformly and performing a first sintering to obtain a first sintering product; Step 4, a small amount of nickel source is configured into a nickel salt solution; a reaction base liquid is added to a reactor, and under stirring, the nickel salt solution, the precipitant solution, and the complexing agent solution are simultaneously added dropwise into the reactor for reaction, and the reaction pH value is controlled at 10 to 12. After the reaction is completed, the nickel precipitate is filtered to separate the nickel precipitate, and the nickel precipitate is washed and dried for later use; Step 5, adding the nickel precipitate to the catechol solution, adjusting the solution to alkalinity, reacting under stirring, and after the coating is completed, slowly adding the zirconium dioxide suspension under stirring to continue the reaction, filtering and separating the solid after the reaction is completed, washing, drying and setting aside; Step 6: Evenly mix the solid product obtained in step 5 and the first sintered product obtained in step 3 and sinter them to obtain a high-throughput power battery positive electrode material; In step 1, a nickel source, a cobalt source, and a manganese source are weighed according to a molar ratio of nickel, cobalt, and manganese of 5 to 8:1 to 2:1 to 3; a lithium source is weighed according to a molar ratio of lithium moles to the total molar number of nickel, cobalt, and manganese of 1 to 1.1:1; the nickel source is divided into two parts of unequal weight, wherein the weight ratio of the large weight part to the small weight part is 7 to 9:1; the nickel source is selected from nickel sulfate or nickel nitrate, the cobalt source is selected from cobalt sulfate or cobalt nitrate, the manganese source is selected from manganese sulfate or manganese nitrate, and the lithium source is selected from lithium carbonate; In step 2, the concentration of the nickel source solution is 1-1.5 mol / L; the concentration of the cobalt source solution is 0.8-1 mol / L; and the concentration of the manganese source solution is 1-1.2 mol / L.
2. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In steps 2 and 4, Reaction base solution configuration: Mix ammonia water and deionized water according to the volume concentration of ammonia water of 1% to 3%, and the mass concentration of ammonia water is 25% to 28%; Precipitant solution configuration: sodium hydroxide aqueous solution with a mass concentration of 25% to 30%; Complexing agent solution preparation: ammonia water with a mass concentration of 15% to 20%.
3. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step 2, the mixed salt solution is added at a rate of 5 to 10 L / min, the precipitant solution is added at a rate of 10 to 20 L / min, and the complexing agent solution is added at a rate of 5 to 20 L / min until the mixed salt solution is completely added.
4. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step three, the first sintering temperature is 500-550°C. First, the furnace temperature is raised to the set temperature at a heating rate of 2-4°C / min, and then the sintering time is maintained at the set temperature for 10-12 hours. In step six, the second sintering temperature is 600-700°C. First, the furnace temperature is raised to the set temperature at a heating rate of 2-4°C / min, and then the sintering time is maintained at the set temperature for 8-10 hours.
5. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step 4, the nickel salt solution is added at a rate of 1 to 3 L / min, the precipitant solution is added at a rate of 2 to 6 L / min, and the complexing agent solution is added at a rate of 1 to 6 L / min until the nickel salt solution is completely added.
6. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: Preparation of the catechol solution in step 5: dissolving catechol in a mixed solution of deionized water and ethanol in a volume ratio of 1 to 2:1, the concentration of the catechol solution is 1 to 2 g / L; the weight ratio of catechol to nickel precipitate is 0.1 to 0.5:1; Configuration of zirconium dioxide suspension: dispersing nano-scale zirconium dioxide in deionized water under ultrasonic conditions; the weight ratio of zirconium dioxide to nickel precipitate is 0.1-0.2:1; the weight ratio of zirconium dioxide to deionized water is 1:40-80.
7. The method for preparing a high-throughput power battery positive electrode material according to claim 1, characterized in that: In step 5, the coating reaction temperature is 30-50°C, and the reaction time is 8-12h; the zirconium dioxide modification reaction temperature is 40-60°C, and the reaction time is 4-6h.
8. A high-throughput power battery positive electrode material, characterized in that: The high-throughput power battery positive electrode material is prepared by the preparation method of any one of claims 1 to 7.
Citation Information
Patent Citations
High-performance lithium ion battery ternary positive electrode material and preparation method thereof
CN110581272A
Preparation method of Li2TiO3 and Li2ZrO3 composite coated ternary cathode material
CN112447946A
Core-shell structure positive electrode material and preparation method thereof
CN112968153A
High-nickel material and preparation method and application thereof
CN113161537A
Multi-element coated core-shell structure lithium ion positive electrode material and preparation method thereof
CN113716549A
